2016
DOI: 10.1111/maps.12716
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral mapping of alteration assemblages within a hydrothermal vug at the Haughton impact structure, Canada

Abstract: Meteorite impacts on Earth and Mars can generate hydrothermal systems that alter the primary mineralogies of rocks and provide suitable environments for microbial colonization. We investigate a calcite–marcasite‐bearing vug at the ~23 km diameter Haughton impact structure, Devon Island, Nunavut, Canada, using imaging spectroscopy of the outcrop in the field (0.65–1.1 μm) and samples in the laboratory (0.4–2.5 μm), point spectroscopy (0.35–2.5 μm), major element chemistry, and X‐ray diffraction analyses. The mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 79 publications
(240 reference statements)
0
7
0
Order By: Relevance
“…Compositional mapping from orbital multispectral data sets at 15-60 m/pixel mapped the regional stratigraphy, crater fill, and uplift within the impact structure (Tornabene et al, 2005) but did not provide definitive mineralogies, distinguish individual clasts, nor observe the near vertical exposures of pristine melt rock. A previous imaging spectroscopy study at the Haughton structure (Greenberger et al, 2016) characterized a hydrothermal calcite-marcasite vug and its weathering products using a more limited wavelength range but did not image or discuss the unaltered melt rock that is the focus of this paper. Carbonate samples from Haughton were measured with point spectroscopy of bulk rock samples and powders in the laboratory for a study of carbonate detection with implications for Mars (Cloutis et al, 2010).…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Compositional mapping from orbital multispectral data sets at 15-60 m/pixel mapped the regional stratigraphy, crater fill, and uplift within the impact structure (Tornabene et al, 2005) but did not provide definitive mineralogies, distinguish individual clasts, nor observe the near vertical exposures of pristine melt rock. A previous imaging spectroscopy study at the Haughton structure (Greenberger et al, 2016) characterized a hydrothermal calcite-marcasite vug and its weathering products using a more limited wavelength range but did not image or discuss the unaltered melt rock that is the focus of this paper. Carbonate samples from Haughton were measured with point spectroscopy of bulk rock samples and powders in the laboratory for a study of carbonate detection with implications for Mars (Cloutis et al, 2010).…”
Section: Geological Settingmentioning
confidence: 99%
“…Samples were collected at all outcrops that were imaged. The methods and instruments used for field measurements in this paper differ from Tornabene et al (2005) and Cloutis et al (2010) and significantly expand on that of Greenberger et al (2016) and therefore are described in full in section 3.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more recently, Young et al (2013) used radiogenic 4 He-based thermochronometers to obtain an Oligocene (~23.5 Ma; U-Th)/He date in zircon, which is resistant to disturbance by postimpact thermal events. Interesting work has also been conducted to study microbe-water-rock interactions in impact-generated hydrothermal alteration assemblages of the HIS as analogs for the habitability of Martian systems (Parnell et al 2004;Izawa et al 2011;Greenberger et al 2016). Another study, by Osinski and Ferri ere (2016), of the HIS shatter cones demonstrated that their distribution is an indicator of the extent of the apparent crater diameter and obliquity of the impact, and that they play a role in reducing the strength of target rocks, thus enhancing crater collapse.…”
Section: History Of Haughton Investigationsmentioning
confidence: 99%
“…2011; Greenberger et al. 2016). Another study, by Osinski and Ferrière (2016), of the HIS shatter cones demonstrated that their distribution is an indicator of the extent of the apparent crater diameter and obliquity of the impact, and that they play a role in reducing the strength of target rocks, thus enhancing crater collapse.…”
Section: Geological Settingmentioning
confidence: 99%